Waning of vaccine-induced immunity to measles in kidney transplanted children. Issue 37 (September 2016) - Rocca, Salvatore; Santilli, Veronica; Cotugno, Nicola; Concato, Carlo; Manno, Emma Concetta; Nocentini, Giulia; Macchiarulo, Giulia; Cancrini, Caterina; Finocchi, Andrea; Guzzo, Isabella; Dello Strologo, Luca; Palma, Paolo
Abstract : Abstract: Vaccine-preventable diseases are a significant cause of morbidity and mortality in solid organ transplant recipients who undergo immunosuppression after transplantation. Data on immune responses and long-term maintenance after vaccinations in such population are still limited. We cross-sectionally evaluated the maintenance of immune response to measles vaccine in kidney transplanted children on immunosuppressive therapy. Measles-specific enzyme-linked immunosorbent assay and B-cell enzyme-linked immunosorbent spot were performed in 74 kidney transplant patients (Tps) and in 23 healthy controls (HCs) previously vaccinated and tested for humoral protection against measles. The quality of measles antibody response was measured by avidity test. B-cell phenotype, investigated via flow cytometry, was further correlated to the ability of Tps to maintain protective humoral responses to measles over time. We observed the loss of vaccine-induced immunity against measles in 19% of Tps. Nonseroprotected children showed signs of impaired B-cell distribution as well as immune senescence and lower antibody avidity. We further reported as time elapsed between vaccination and transplantation, as well as the vaccine administration during dialysis are clinical factors affecting the maintenance of the immune memory response against measles. Tps present both quantitative and qualitative alterations in the maintenance of protective immunity to measles vaccine. Prospective studies are needed to optimize the vaccination schedules in kidney transplant recipients in order to increase the immunization coverage over time in this population.